PENGARUH MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP AL MINHAJ TAMANSARI - Titi Tri Lestari; Attin Warmi (IKIP Siliwangi, 2023)
This research was conducted to knowing the effect of the Missouri Mathematics Project (MMP) learning model on student’s mathematical creative thinking abilities. This research uses a quantitative approach with a quasi-experimental method. The population of this research were all students of SMP Al Minhaj Tamansari. The research sample was students of class VIII E who became the control class and students of class VIII D who became the experimental class. Samples were taken by simple random sampling technique. Research data collection was taken by the test method. The test instrument used contains 4 questions that have been tested for validity and reliability. Data analysis begins with prerequisite test, namely normality test and homogeneity test. After that, the hypothesis is tested using the two-average difference test or t test. The results of data analysis found that there were differences in mathematical creative thinking skills between students who studied with the Missouri Mathematics Project (MMP) model and students who studied with conventional methods.